Strong Associations Between Childhood Victimization and Community Violence in Male Forensic Mental Health Patients - Fosse, Roar; Eidhammer, Gunnar; Selmer, Lars Erik; Knutzen, Maria; Bjørkly, Stål (Frontiers in Psychiatry, 2021)
Background. Childhood victimization increases the risk of both mental disorders and violent behavior. Associations between child victimization and violent behavior have not been extensively investigated in forensic mental health settings. We asked whether the extent of childhood victimization predicts the extent of violence in the community in forensic mental health patients. Methods. We included 57 patients (52 male) at a medium security forensic mental health ward, with diagnoses of predominantly paranoid schizophrenia and other schizophrenia and psychotic disorders. Seventy-five percent had comorbid substance abuse. We used the Maltreatment Abuse Chronology of Exposure (MACE) scale to identify and score sexual, physical and emotional abuse, emotional and physical neglect, witnessing violence, and bullying based on information in electronic patient journals. We used information from the same source to assess war trauma, interpersonal violence in the community, sexual assault, acts of arson, and homicide prior to admissions. Results. Physical and emotional abuse, emotional/ physical neglect, and bullying were associated with higher levels of community violence. Childhood adversities were also associated with arson and sexual assaults but not with homicide. We observed a linear, significant increase in the frequency of community violence with increasing numbers of victimization types. Conclusions. The most violent forensic mental health patients had the most extensive histories of childhood victimization. An enhanced focus on the extent of childhood victimization in risk assessment and management of violence may be considered in forensic inpatient settings.